Is thrombocytosis a valid indicator of advanced stage and high mortality of gynecological cancer? - Rathod, Archana D.; Deshmukh, Varsha; Kodgire, Jyoti (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Cytokines that stimulate thrombopoiesis are often elevated in cancer, and as a result, various cancers have been associated with thrombocytosis. In addition thrombocytosis has been found to be an adverse prognostic factor in many types of common cancers. Methods: A cross sectional study was designed to evaluate the factors associated with prognosis of the cases of carcinoma cervix in the Department of Gyne-Oncology, GMCH, Aurangabad from August 2016 to August 2017. Variables analysed were the sociodemographic details, literacy level, symptoms, duration, stage of the disease at diagnosis, pretreatment platelet counts were noted. Results: 85% patients were having squamous cell carcinoma, 6 % patients were having adenocarcinoma and 9% patients had adenosuamous carcinoma. 29% patients have platelet count less than 3 lakhs and 18 patients has tumour less than 4 cm. 71 % patients have platelet count more than 3 lakhs, only 6% patients belonged to early stage and 65% belonged to late stage of cancer cervix. Conclusions: Seventy one percent of the cases had platetlet count >3 lakh, of which only 6% were in early stage of disease, whereas 65% belonged to late stage of the disease. All the patients with tumour size of >4 cm had platelet count more than 3 lakh, this shows strong association of platelet count with tumour size >4 cm and advanced stage of the disease. This can be used as independent prognostic factor for prognosis of cancer cervix.